Estimation of the second ventilatory threshold through ventricular repolarization profile analysis - Milagro, J.; Hernández-Vicente, A.; Hernando, D.; Casajús, J. A.; Garatachea, N.; Bailón, R.; Pueyo, E. (Scandinavian Journal of Medicine & Science in Sports, 2021)
Under the hypothesis that sympathetic control of ventricular repolarization may change once the second ventilatory threshold (VT2) has been reached, a novel methodology for non-invasive VT2 estimation based on the analysis of the T wave from the electrocardiogram (ECG) is proposed, and potential underlying physiological mechanisms are suggested. 25 volunteers (33.4 ± 5.2 years) underwent an incremental power cycle ergometer test (25 W/minute). During the test, respiratory gas exchange and multi-lead ECG were acquired. The former was employed to determine VT2, used here as a reference, whereas the latter was used to compute the temporal profiles of an index of ventricular repolarization instability (dT) and its low-frequency (LF) oscillations (LFdT). The sudden increases observed in dT and LFdT profiles above an established heart rate threshold were employed to derive VT2 estimates, referred to as VT2dT and VT2LFdT, respectively. Estimation errors of -4.7 ± 25.2 W were obtained when considering VT2dT. Errors were lower than the one-minute power increment of 25 W in 68% of the subjects and lower than 50 W in 89.5% of them. When using VT2LFdT, estimation error was of 15.3 ± 32.4 W. Most of the subjects shared common characteristic dT and LFdT profiles, which could be reflecting changes in the autonomic control of ventricular repolarization before and after reaching VT2. The analysis of ventricular repolarization dynamics during exercise allows non-invasive ECG-based estimation of VT2, possibly in relation to changes in the autonomic control of ventricular electrical activity when VT2 is reached.